Numerical Simulation of Lyophilization of Carrot Slices at Atmospheric Pressure in a Fluidized Bed - Reyes-Salinas, A; Mahn-Osses, A; Quijada-Maldonado, E; Bubnovich, V (2012)
Two-dimensional numerical simulations were carried out to describe the lyophilization process at atmospheric pressure and its optimization. The finite differences method succeeded in describing correctly the complex motion of the sublimation interface in foodstuff. Comparison of unidirectional and bidirectional mass and energy transport showed considerable differences in the drying kinetics. These differences decreased as the geometric ratio (GR) decreased and the physical situation approached to that of an infinite plate. The temperature and vapor pressure distributions were analyzed as functions of ice saturation. Two-dimensional numerical simulations showed a good fit with the experimental data. © 2011 Elsevier B.V. All rights reserved.